Serological profile of convalescent COVID-19 patients at an infectious diseases hospital in Nigeria (2021)
Background: IgG antibodies may serve as promising targets to detect and evaluate immune responses against the SARS-CoV-2 virus. Both IgA and IgM antibodies target the spike protein’s receptor binding domain and are rapidly decayed, while IgG antibodies remain relatively stable for longer periods in COVID-19 patients. Objectives: The current study was designed to detect the presence of SARS-CoV-2 antibodies among convalescent COVID-19 patients and to evaluate the relationship between these antibodies, the symptom grade and their baseline Cycle Threshold (CT) by RT-PCR. Methods: Eighty-nine convalescent COVID-19 patients on admission were recruited and tested until negative by RT-PCR. Sera obtained from participants were screened for SARS-CoV-2 IgM and IgG antibodies using rapid lateral flow assays. Results: It was observed that 93,3% and 77,5% respectively had IgM and IgG antibodies against the S1 protein of SARS-CoV-2. Majority (74,0%) presented with mild COVID-19 symptoms with a mean RT-PCR Ct value of 31,4. Conclusion: Convalescent COVID-19 patients develop a fairly good level of IgG antibodies. Theantibody status is not dependent on CT value or symptom grade. However, there was a significant correlation between baseline CT and time taken to test negative by RT-PCR.